Piperonylbutoxide and the Necessity of Toxicological Assessment of Insecticide Mixtures; a Letter to Editor - Habedank, Dirk; Habedank, Birgit (Archives of Academic Emergency Medicine, 2024)
With great interest we read the letter by Dr. Faress et al. (1) in which they explain the clinical impression of pyrethroid poisoning in relation to the addition of piperonylbutoxide (PBO). The authors include our case report of an insecticide spray formulation containing cypermethrin, tetramethrin and PBO that induced a myocardial infarction type II in a patient with cardiac comorbidity (2). We fully agree with the authors that the “presence or absence of piperonylbutoxide” may induce different types of pyrethroid poisoning and determination of all suspicious ingredients is “necessary for all clinical toxicologists”. However, we think it is necessary to discuss the current assessment of PBO, and to analyze in detail some of the case reports cited.